Cryptanalysis of IAR-CTR and IAR-CFB and a fixing method - Xueqi Zhu; Fangzhou Liu; Yan Jia; Jun Xu; Peng Wang (Cybersecurity)
Abstract We present practical attacks on IAR-CTR and IAR-CFB, AE modes proposed by Hwang and Gope to offer both privacy and authenticity in a single pass. Then we use the idea of iCOFB, which is originally defined with a tweakable random function, to fix the IAR-CTR mode using the tweakable block cipher, and propose the TIAR-CTR mode, which is a one-pass AEAD mode with provable security. However, the same fixed method does not work for the IAR-CFB mode.